THE PLACE OF ENTREPRENEURSHIP AND EMPLOYMENT - Alumona Chukwuma, Stephen (CENTRAL ASIA AND THE CAUCASUS, 2024)
The role of entrepreneurship intention has been acknowledged to be relevant in managerial, intentions can predict individual behavior and organizational outcome. Entrepreneurship education is a purposeful intervention by an educator in the life of the learner to impact entrepreneurial qualities and skills to enable the learner to survive in the world of business. The study used the primary and secondary sources of data collection In the course of study, relevant literature in both was reviewed. In the methodology, the questionnaire method was used to draw out relevant information from respondents which were guided by certain hypothesis based on the set objectives of the work the study came to the conclusion and recommendations that any work that aims to improve the entrepreneurial intention of young university students should address the issue of changing the mentality of these graduates from earning to making profits.